Método de apuração de custos e formação de preços: serviços de locação de veículos - Castro, Miguel Arcanjo de (2023)
Cost management is a crucial instrument for public and private organizations to identify and control their expenses related to the activities of delivering services and products to society. For the purposes of this cost calculation and price formation study, the chosen activity is transporting the fleet leased by the company Locação Brasil LTDA to the municipality of Fortaleza, a common activity in the areas of transport and logistics. It has a value of approximately R$60,000,000.00 (Sixty million) per year, requiring the correct calculation of costs to guarantee the efficiency and legality of its management. The tool for calculating and analyzing costs, demonstrated in a spreadsheet (Figure 2, page 32), uses the Direct Costing and Absorption Costing methodology, (page 16, item 3) where financial and tax assumptions are directed to the vehicle rental services, which can be adapted to another service or product model. The research was prepared based on the clauses of the Service Provision Contract signed between the PMF (Fortaleza City Hall) and the company Locação Brasil LTDA, with interviews with the managers of the respective companies. Vehicle acquisition prices were used based on the FIP table and the interest assumptions of the Central Bank of Brazil. The tax application applied according to the National tax framework – Data from the Ministry of Finance, Federal Government portal. The Absorption Costing and Direct Costing methods are based on economic-financial science, with emphasis on the cost concepts covered in the disciplines of Microeconomics, Macroeconomics, Financial Mathematics and Cost Accounting. To find the price of rental services for each object, the methods mentioned are used and the mark-up is applied as shown on page 27, table 4. From the perspective of the tool suggested here, the total annual contracted value could be lower at R$ 4.53 million reais, an amount that could be used in a delivery in the healthcare area, for example.